One risk assessment for genetically modified plants - Koch, Muffy; DeMond, Jaylee; Pence, Matthew G.; Schaefer, Elena A.; Rudgers, Gary (Frontiers in Bioengineering and Biotechnology, 2025)
With over 30 years’ experience conducting risk assessments for genetically modified (GM) plants, regulatory agencies that review the safety of GM plants understand the potential food, feed, and environmental risks associated with these products. This vast regulatory experience is underutilized when risk assessments for GM plants are repeated on a per-country basis. The redundancy in country-by-country reviews of the same GM plants places a disproportionate regulatory burden on developers and strains limited government resources for conducting safety reviews. Requiring repeated, multi-country risk assessments to obtain food and feed import permits or cultivation permits for GM plants is unnecessary as repeated assessments do not change the safety and associated risks of already approved products. To avoid redundancies in the regulation of GM plants, we propose adoption of one, global risk assessment for food, feed, and environmental release carried out to international standards. Our proposed model for one global risk assessment encourages the sharing of food, feed and environmental risk assessment summaries between countries while maintaining national approvals for GM plants. Steps towards a streamlined and efficient review process for GM plants are discussed, including implementing a global, forward-looking approval process that eliminates repetitive risk assessments and re-reviews of low-risk traits. Harmonization of risk assessment is an achievable goal that would accelerate regulatory approvals and enable broader access to the benefits of GM plants which are currently only available to some countries.